The Effect of Factoring Implementation on Working Capital of PT. Duo Nadenggan Lestari - Darwin Darwin; Renny Maisyarah; M. Irsan Nasution (Utan Kayu Publishing, 2025)
This study aims to examine the effect of factoring implementation on working capital at PT. Duo Nadenggan Lestari. Factoring is utilized as an alternative financing method to accelerate cash inflows by converting accounts receivable into immediate funds, thereby supporting the company’s liquidity. This research adopts a quantitative approach using secondary data derived from the company’s financial statements over a specific period. Data analysis is conducted using simple linear regression to determine the influence of factoring implementation as the independent variable on working capital as the dependent variable. The results of the analysis indicate that factoring implementation has a positive and significant effect on working capital. An increase in factoring utilization contributes to improved cash flow, enhanced liquidity, and more efficient working capital management. These findings suggest that factoring can be an effective financial strategy for companies experiencing cash flow constraints and high receivables levels. The study provides practical implications for management in selecting appropriate financing alternatives to strengthen short-term financial performance